PERIOPERATIVE ACUTE KIDNEY INJURY AFTER MAJOR NON-CARDIAC SURGERY: RISK FACTORS, CLINICAL OUTCOMES, AND PREDICTIVE PERFORMANCE OF PERIOPERATIVE SCORING SYSTEMS - Sekulic, Ana; Marinkovic, Olivera; Milic, Danilo (Medical Research, 2026)
Background: Perioperative acute kidney injury (AKI) is a serious complication after major non-cardiac surgery, associated with increased mortality, prolonged ICU stay, and the need for renal replacement therapy (RRT). Objective: To assess the impact of AKI severity and associated risk factors on clinical outcomes after major abdominal surgery and to evaluate the prognostic performance of SPARK, APACHE II, and SOFA scores, including sepsis-associated AKI. Materials and Methods: This prospective cohort study was conducted in the Surgical ICU of University Hospital Center Bežanijska Kosa (Belgrade) from January to June 2024. Thirty adult patients who developed perioperative AKI after major abdominal surgery were analyzed. AKI was defined according to KDIGO criteria and sepsis according to Sepsis-3. Disease severity was assessed using APACHE II and SOFA, and preoperative AKI risk using the SPARK index. Results: AKI occurred in 30 operated patients. KDIGO stages were: stage 1 in 26.7%, stage 2 in 30.0%, and stage 3 in 43.3%. In-hospital mortality was 30.0% and occurred exclusively in patients older than 60 years. Mortality was significantly higher in KDIGO stage 3 (61.5% vs. 5.9%, p=0.0016). KDIGO stage 3 and age >60 years were strongly associated with death. SPARK showed good discrimination for severe AKI (AUC≈0.78), while APACHE II demonstrated excellent performance for severe AKI and mortality (AUC≈0.97). RRT use was more frequent in advanced AKI stages. Conclusions: Perioperative AKI was infrequent but severe, with high mortality driven by KDIGO stage 3 and advanced age. SPARK and particularly APACHE II were useful for risk stratification.